Back to the Future : The Nature of Regulatory Capital Requirements - Chami, Ralph (IMF Working Papers; Working Paper ;, 2017)
This paper compares the current regulatory capital requirements under the Dodd-Frank Act (DFA) and the 10-percent leverage ratio, as proposed by the U.S. Treasury and the U.S. House of Representatives' Financial CHOICE Act (FCA). We find that the majority of U.S. banks would not qualify for an "off-ramp"option-where regulatory relief is offered to FCA qualifying banks (QBOs)-unless considerable amounts of capital are added, and that large banks are much closer to the proposed leverage threshold and, therefore, are more likely to stand to gain from regulatory relief. The paper identifies an important moral hazard problem that arises due to the QBO optionality, where banks are likely to increase the riskiness of their asset portfolio and qualify for the FCA 'off-ramp' relief with unintended effects on financial stability.